Reassessing Global Monetary Governance: IMF, Dollar Hegemony, and the Quest for Economic Justice in a Fragmented Global Order - Syah Muhammad Mousa Al Zaki (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
This article analyzes the structural limits of contemporary global monetary governance amid rising geopolitical tensions, expanding economic sanctions, and renewed debates on de-dollarization and monetary sovereignty. While international monetary law is often presented as a neutral framework aimed at ensuring stability and cooperation, recent developments suggest a system increasingly marked by asymmetrical power, legal fragmentation, and distributive inequality. Drawing on a Law and Political Economy (LPE) perspective, this study argues that the dominance of the United States dollar and the institutional role of the International Monetary Fund (IMF) are not merely economic outcomes, but reflect a legalized hierarchy embedded in global monetary governance. Methodologically, the research combines doctrinal legal analysis with a policy-oriented approach, focusing on soft law instruments, institutional design, and governance practices. The analysis shows that monetary infrastructures and legal norms enable the strategic use of financial sanctions, thereby constraining monetary sovereignty and limiting policy space for many states. In this context, de-dollarization and calls for monetary autonomy are better understood not simply as economic or political responses, but as legal critiques of an unequal global order. This study contributes to international economic law by advancing a reform-oriented perspective that emphasizes monetary pluralism, seeks to limit asymmetric power, and calls for greater accountability and economic justice.